PENGARUH METODE LATIHAN AGILLITY TERHADAP KECEPATAN TENDANGAN SABIT - Adnadia, Fitri Devi; Purnomo, Edi; Haetami, Mimi (Universitas Tanjungpura, 2022)
AbstractThe purpose of this study was to determine the effect of the Agility training method on the speed of the sickle kick at the Cuyusika Bangau Putih Pencak Silat College. This study used an experimental method with pretest and posttest treatments to determine the difference in numbers before and after being given treatment. The design used in this study was a one group pretest and posttest design. The sample in this study was the pencak silat athletes from the Cuyusika white stork college, totaling 20 athletes. The data analysis technique used is the t test performed with SPSS 21 calculation which has a significance provision and an acceptance or rejection area of 5% or 0.05. The results showed an average pretest result of 0.34 and an average posttest result of 0.29, from an increase in kick speed from the average value of the pretest and posttest an increase of 14.71%